Evaluative Conditioning Induces Changes in Sound Valence - Bolders, Anna C.; Band, Guido P.; Stallen, Pieter Jan (Frontiers in Psychology, 2012)
Evaluative Conditioning (EC) has hardly been tested in the auditory domain, but it is a potentially valuable research tool. In Experiment 1 we investigated whether the affective evaluation of short environmental sounds can be changed using affective words as unconditioned stimuli (US). Congruence effects on an affective priming task (APT) for conditioned sounds demonstrated successful EC. Subjective ratings for sounds paired with negative words changed accordingly. In Experiment 2 we investigated whether the acquired valence remains stable after repeated presentation of the conditioned sound without the US or whether extinction occurs. The acquired affective value remained present, albeit weaker, even after 40 extinction trials. These results warrant the use of EC to study processing of short environmental sounds with acquired valence, even if this requires repeated stimulus presentations. This paves the way for studying processing of affective environmental sounds while effectively controlling low level-stimulus properties.